Inclusion and Social Justice in Mexico. What can be done from an Educational Perspective? - Pérez Archundia, Eduardo (2019)
Mexico is currently undergoing a social crisis. On the one hand, it experiencing alternating elections which many consider to be the advent of a new form of politics which also brings with it the hope of ending poverty, insecurity and deterioration of the educational system. Based on this scenario, this article discusses premodern conditions that are prevalent in Mexico and which have obstructed the development of the country´s economy, educational and social security sectors. It also highlights the complexity of the different types of factors that  involved in social deterioration. The article questions how poverty, crime and education are superimposed and emphasizes the need to contain high school drop-out rates which are tied to difficulties in entering the job market and its consequential relationship to poverty. Dropping out of school also encourages youngsters to commit crimes. Education is perceived as one of the solutions to fight crime and poverty – however, not education as it currently stands. Academic problems would first have to be resolved, such as preventing school dropouts in both High School and College as well as improving coverage, which requires a differentiated type of education.